Implementation of Fiqh Learning with a Habituation Learning Approach in Grade II Students of Madrasah Ibtidaiyah Ihyaul Islam Pakuniran Probolinggo - Siti Sholehah; Ainur Rofiq Sofa (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to describe the implementation of Fiqh learning using a habituation learning approach for second-grade students at MI Ihyaul Islam Pakuniran, focusing on its implementation, evaluation, learning novelty, and supporting and inhibiting factors. This research employed a qualitative case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, Fiqh teacher, foundation chairman, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that Fiqh learning based on habituation learning improves students’ understanding and practice of worship. Learning activities are not limited to classroom instruction but are strengthened through consistent daily worship habituation. The novelty of this study lies in the application of micro-habituation learning, which consists of small, brief, and routine worship practices suited to lower-grade students’ characteristics. Learning evaluation is carried out through practical assessment and observation of religious attitudes. Supporting factors include teachers’ role modeling and a strong religious culture, while inhibiting factors involve differences in students’ religious habits at home.